Advances in library administration and organization. Vol. 30 - Williams, Delmus Eugene; Golden, Janine (Bingley, U.K. : Emerald, 2011)
As it continues to publish work that is relevant for both researchers and library practitioners, Volume 30 of Advances in Library Administration and Organization contains articles describing efforts at cooperation and collaboration within the library profession. This volume includes scholarship that illustrates both concepts, best defined in one of the chapters as terms'often used loosely to describe relationships among entities or people working together.' Topics explored within the volume include an examination of public and academic libraries as places that provide purposeful spaces specific to providing user need fulfilment; library services in juvenile detention centers; and the contribution of school library media specialists. The development of electronic institutional repositories, primarily in academic libraries and based on efforts to encourage campus community involvement and partnerships between librarians and the faculty they serve is discussed. Successful fund raising in libraries is explored through the examination of the impact of organizational placement of the library development officer in universities.
A critical analysis of the discourse on academic libraries as learning places / Catherine Closet-Crane -- The rural public library as place : a theoretical analysis / Linda R. Most -- A framework for institutional repository development / Jennifer Campbell-Meier -- Interagency cooperation in juvenile detention center library services : an introduction to the issues / Jennifer K. Sweeney -- Perceptions of school library media specialists regarding the practice of instructional leadership / Virginia D. Martin -- The perceptions of high school teachers on the roles and responsibilities of library media specialists / Kelli Steverson Ragle.
Keywords: Library administration